Women Movement in Modern Pakistan Found in Novel “I Am Malala” - Sri Lestrawati Tampubolon; Robby Satria Mandala (LPPM Universitas Bumigora Mataram, 2021)
This study discusses the bad conditions experienced by women in Pakistan and their actions to fight for these conditions in the modern era as seen in the novel